HUBUNGAN DIGITAL DISTRACTION TERHADAP KONSENTRASI BELAJAR SISWA KELAS V SDN GENUKSARI 01 - Amsiyah, Siti; Ulia, Nuhyal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study, entitled The Relationship between Digital Distraction and the Concentration of Fifth Grade Students at SDN Genuksari 01, is motivated by the development of the digital era, which has facilitated the acquisition of information and learning resources. However, technology has also created a problem known as digital distraction, which has the ability to disrupt student concentration. Digital distraction occurs when students' attention is diverted from learning activities to the use of digital devices for non-academic purposes. The purpose of this study is to determine the relationship and influence of digital distraction on student concentration. This study uses a quantitative approach with a correlational methodology. The sample size is 52 students, selected using a saturated sampling method. Data were collected using a questionnaire about digital distraction and learning concentration, which has been validated and is reliable. Data were analyzed using descriptive statistics, normality tests, linearity tests, Spearman's Rank correlation test, and simple linear regression. Theoretically, this study is based on the theory of cognitive load and self-regulated learning, which explains how digital distraction affects students' attention and self-control processes during learning. The results show that digital distraction and student concentration have a moderate influence. The correlation test resulted in -0.194, indicating a very weak and negligible negative relationship (p > 0.05). Regression tests revealed that digital distraction had no significant effect on learning concentration (p = 0.092; contribution: 5.6%). Based on these findings, it was concluded that digital distraction was not the primary factor affecting students' learning concentration. Therefore, it is important to manage technology properly while strengthening internal elements and creating an effective learning environment.